A randomized trial of the efficacy and safety of azilsartan medoxomil combined with chlorthalidone. (September 2018) - Weber, Michael A; Sever, Peter; Juhasz, Attila; Roberts, Andrew; Cao, Charlie
Introduction: We measured the effects of azilsartan medoxomil co-administered with chlorthalidone 25 mg in stage 2 hypertension. Methods: Azilsartan medoxomil 40 or 80 mg plus chlorthalidone were compared with placebo plus chlorthalidone once daily in a randomized, double-blind, 6-week trial. The primary endpoint was change from baseline in 24-hour mean systolic blood pressure by ambulatory blood pressure monitoring. Results: Patients ( N =551; mean age 59 years; 51.7% men) were randomly assigned to placebo plus chlorthalidone ( n =184), azilsartan medoxomil 40 mg plus chlorthalidone ( n =185), or azilsartan medoxomil 80 mg plus chlorthalidone ( n =182). Baseline systolic blood pressures were similar among groups. After 6 weeks, least squares mean (standard error) reductions with azilsartan medoxomil 40 mg and 80 mg plus chlorthalidone were similar in magnitude (−31.7 (1.0) and −31.3 (1.0) mmHg, respectively), but greater than chlorthalidone alone (−15.9 (1.0) mmHg). Hypotension and serum creatinine elevations were more frequent with azilsartan medoxomil plus chlorthalidone than chlorthalidone alone (reversed with drug discontinuation). Notably, plasma potassium reduction of 0.43 meq/L with chlorthalidone was attenuated to 0.13 and 0.05 meq/L by azilsartan medoxomil 40 mg and 80 mg, respectively. Conclusion: Azilsartan medoxomil 40 mg or 80 mg plus chlorthalidone 25 mg was significantly more efficacious than chlorthalidone alone in reducing blood pressure and was well tolerated. Clinicaltrial.gov, https://clinicaltrials.gov/ct2/show/NCT00591773, NCT00591773